2021
DOI: 10.1029/2019tc005932
|View full text |Cite
|
Sign up to set email alerts
|

Underthrusting of the Tarim Lithosphere Beneath the Western Kunlun Range, Insights From Seismic Profiling Evidence

Abstract: Continental underthrusting is one of mechanisms of growth of the Tibetan Plateau (Meyer et al., 1998; Tapponnier et al., 2001). Quantifying it over the tens-of-millions-year time scale remains challenging. For the Indian subcontinent that is currently connecting with the active Indian Ocean mid-ridge, its underthrusting rates can be estimated by sea floor magnetic lineations (Molnar & Tapponnier, 1975). Yet, for parts of the Asian continent which passively underthrusted southwards beneath the Tibetan Plateau i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…This would be in line with the findings at the scale of our investigated area where the shortening absorbed north of the Tiklik thrust increases from ∼35 to ∼64 km westward (Figure 7). This is also suspected at a much larger scale when compared to some of the cross sections published west of our study area (e.g., Jiang et al, 2013;Wang et al, 2021).…”
Section: Exploring Possible Kinematic Changes At the Scale Of The Wes...mentioning
confidence: 59%
See 3 more Smart Citations
“…This would be in line with the findings at the scale of our investigated area where the shortening absorbed north of the Tiklik thrust increases from ∼35 to ∼64 km westward (Figure 7). This is also suspected at a much larger scale when compared to some of the cross sections published west of our study area (e.g., Jiang et al, 2013;Wang et al, 2021).…”
Section: Exploring Possible Kinematic Changes At the Scale Of The Wes...mentioning
confidence: 59%
“…Five major anticlines are recognized in this outer part of the range, from west to east: the Yecheng‐Pishan, Kekeya, Fusha, Pusikai, and Hotan anticlines (Figure 1c). They mainly correspond to blind imbricated thrusts and duplex structures (e.g., Guilbaud et al., 2017; Laborde et al., 2019; Li et al., 2021; Sun et al., 2019; Wang et al., 2016, 2021), as well as to one large blind ramp anticline known as the Hotan anticline (Cheng et al., 2017; Jiang et al., 2013). These structures develop where the shortening is transferred upward from the lower detachment in the middle to upper Cambrian series to the shallowest one at the base of the Cenozoic Tarim strata.…”
Section: Geological Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Some workers suggested that rigid Tarim block at the northern margin and the Sichuan basin in the eastern flank are pushed northward and eastward, respectively in the course of the India‐Asia collision (Pan & Shen, 2017; S. Wang, Chen, et al., 2021). In fact, the GPS observations support this hypothesis (Liang et al., 2013; Zhang et al., 2004).…”
Section: Limitations and Future Scopesmentioning
confidence: 99%